2021
DOI: 10.9745/ghsp-d-20-00361
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Breastfeeding in Low- and Middle-Income Countries: A Time-to-Event Analysis

Abstract: We calculated a continuous measure of time to initiation of breastfeeding in low-and middle-income countries using recent Demographic and Health Surveys Program data and found that although the average time ranged from 1.7 hours in Burundi to 40 hours in Chad, the median time to initiation met the benchmark of within 1 hour in most countries.n In nearly all countries studied and after controlling for confounding factors, cesarean delivery was associated with a significant delay in median time to initiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Previous studies using multi-country data described similar findings of delay in EIBF among c-section births compared to institutional vaginal delivery 6 , 7 , 26 . In WHO Global Survey data of 373 health facilities and 244,569 singleton live births of low obstetric risk pregnancy, c-section was an independent factor associated with delay in EIBF 6 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous studies using multi-country data described similar findings of delay in EIBF among c-section births compared to institutional vaginal delivery 6 , 7 , 26 . In WHO Global Survey data of 373 health facilities and 244,569 singleton live births of low obstetric risk pregnancy, c-section was an independent factor associated with delay in EIBF 6 .…”
Section: Discussionsupporting
confidence: 61%
“…In WHO Global Survey data of 373 health facilities and 244,569 singleton live births of low obstetric risk pregnancy, c-section was an independent factor associated with delay in EIBF 6 . In another study in 21 LMICs, although deliveries by c-section presented a significant delay in the median of EIBF, immediate skin-to-skin contact was associated with a shorter time for breastfeeding initiation in almost all countries 7 .…”
Section: Discussionmentioning
confidence: 87%
“…Globally, it has been shown that breastfeeding has prodigious benefits for both mothers and newborns. It supports the child's growth, protects the child against infections and the mother from post‐partum haemorrhage and breast and ovarian cancers (Ekholuenetale et al, 2021 ; Mallick et al, 2021 ; Rollins et al, 2016 ; Victora et al, 2016 ). It is estimated that breastfeeding can save up to a million deaths in children under age five each year (Victora et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in low- and middle-income countries, the breastfeeding initiation rate in the first hour is lower [ 12 ]. In these countries, the initiation time between 0.5 and 40 hours after birth has been estimated [ 13 ]. In Latin America and the Caribbean, the prevalence of EIBF was 45.2–62.8% [ 14 ], while the prevalence of EBF up to 6 months was 63.0% [ 15 ].…”
Section: Introductionmentioning
confidence: 99%